m6A Modification Involves in Enriched Environment-Induced Neurogenesis and Cognition Enhancement - Qu, Wenzheng; Li, Qian; Wang, Mengxuan; Zhao, Xingsen; Wu, Jiangdong; Liu, Diwen; Hong, Shenghui; Yang, Ying; Shu, Qiang; Li, Xuekun (Frontiers in Cell and Developmental Biology, 2022)
Although previous studies have shown that enriched environment (EE) promotes neurogenesis and alters DNA and histone modifications, it remains largely unknown whether enriched environment affects epitranscriptome in the context of neuronal development. Here, we showed that EE exposure enhanced the pool of adult neural stem/progenitor cells (aNSPCs) and promoted neuronal differentiation of aNSPCs. EE exposure also improved cognitive capabilities and altered the expression of genes relating to neuronal development, neurogenesis, and memory. N6-methyladenosine (m6A) immunoprecipitation combined with deep sequencing (MeRIP-seq) data analysis revealed that EE exposure increased the global level of m6A and led to differential m6A mRNA modification. Differential m6A modification-associated genes are involved in neuronal development, neurogenesis, etc. Notably, EE exposure decreased the protein level of m6A eraser Fto, but did not affect the protein level of m6A writers Mettl3 and Mettl14. Taken together, our results suggest that enriched environment exposure induces differential m6A mRNA modification, and add a novel layer to the interaction between environment and epigenetics in the context of the postnatal neuronal development.